URGENSI DAN PROSPEK PENGATURAN (IUS CONSTITUENDUM) UU TENTANG CONTEMPT OF COURT UNTUK MENEGAKKAN MARTABAT DAN WIBAWA PERADILAN - Mulyadi, Lilik (Jurnal Hukum dan Peradilan, 2015)
Contempt of court law is urgent, immediately, and urge, so need critically, academicly, and comprehendship analyzing and research to protect the honour and uphold the dignity and souverignty of the courtKeywords : Ius Constituendum, Contempt of Court, Court Dignity